Pediatric ultrasound-guided dorsal penile nerve block and sedation in spontaneous breathing: a prospective observational study - Dottore, Bruno; Meroi, Francesco; Tomasino, Serena; Orso, Daniele; Comuzzi, Matteo; Vernaccini, Nicola; Vetrugno, Luigi; Intini, Sergio; Bove, Tiziana (Frontiers in Medicine, 2023)
Background: Worldwide, one of the most common surgical procedures in the pediatric population is circumcision. There is no consent on the best anesthesiologic approach. This study aims to investigate ultrasound-guided dorsal penile nerve block (DPNB) plus sedation in spontaneous breathing as a time-saving, safe, effective, and opioid-sparing technique.Aims: The primary outcome was the assessment of the time from the end of surgery and the discharge to the post-anesthesia care unit. Secondary outcomes were to evaluate the cumulative dosages of opioids, differences in pain levels between the two groups, and complications at the awakening, 4 hours after surgery and 72 hours after surgery.This was a prospective study with a retrospective control group, approved by the Friuli-Venezia Giulia Ethics Committee. Children in the intervention group received an ultrasound-guided DPNB under sedation and spontaneous breathing. With the probe positioned transversally at the base of the penis using an in-plane approach with a modified technique, local anesthetic was injected under the deep fascia of the penis.: We included 70 children who underwent circumcision at the University-Hospital of Udine, Italy from January 1, 2016, to October 1, 2021. 35 children in the ultrasound-guided DPNB group and 35 children in the control group. Children who received ultrasound-guided DPNB had a statistically significant lower time to discharge from the operating room, did not require mechanical ventilation, maintained spontaneous breathing at all times, received fewer opioids, had lower mean intraoperative arterial pressures, and lower pain levels immediately after surgery. Conclusion: ultrasound-guided DPNB associated with sedation and spontaneous breathing is a time-saving, opioid-sparing, safe and effective strategy for the management of intra-and postoperative pain in children undergoing circumcision.